The Role of the Counsellor in the Human Resources Planning - Bossi, Carolyn; Hobelaid, Ena (Canadian Journal of Counselling and Psychotherapy, 2011)
In response to external and internal factors which have forced post-secondary educational institutions to assess the management of their human resources, one Ontario college is requiring all of its employees to develop Individual Professional Development Plans (IPDP) which meet with individual, departmental, and institutional goals. This article describes how the counsellors of the college meet individually with employees to determine the nature of these plans and to assist them in determining the most effective means of achieving their goals in a proactive, non-punitive approach.